Anak Indonesia Pencipta AI untuk Pendidikan - Melvinda Dewi Kirana; Masduki Asbari; Risma Rusdita (AGUSPATI RESEARCH INSTITUTA, 2024)
The aim of this study is to determine technological developments, namely artificial intelligence or often called AI (Artificial Intelligence). In this study report, a descriptive qualitative method was used by taking notes because the data source was obtained by listening to the oral narrative from Helmy Yahya Talk's YouTube channel entitled